PROFIL KINERJA FINANSIAL PERUSAHAAN-PERUSAHAAN YANG GO-PUBLIC DI PASAR MODAL ASEAN - Mas'ud Machfoedz (Journal of Indonesian Economy and Business (JIEB), 1999)
Almost all companies listed in ASEAN country capital markets have droppedtheir financial performance since the accounting year of 1997. In Indonesia, morethan sixty per cent of companies listed in Jakarta Stock Exchange did not or did notdare to publish their mandatory annual financial statements to avoid publishing theirpoor performance. The similar situation has also been felt by other ASEAN countrycapital markets. The question that was relevant to be raised: are the poor financialperformance of companies listed in the ASEAN country capital markets caused by thesudden crisis or by long experience of poor financial performance?This study intents to answer the above question, whether the crisis or longtimeof poor financial performance caused the company financial problems. Samples weretaken from companies listed in four major capital market of ASEAN, namely:Thailand, Singapore, Malaysia, and Indonesia. Pooled time series data consist of 132data included in the sample for three year periods of 1993, 1994, and 1995 for 44companies. The parametric and non-parametric statistic methods q/"t-tests, WilcoxonRanks Sign Test, MANOVA, and Friedman K-Samples were used to test thehypothesis.The results indicate that Thailand has the weakest financial performance,followed by Indonesia, Singapore, and then Malaysia, when they are compared to theempirical standards of financial performance. This study used The standards offinancial performance that were introduced by Beaver (1966 and 1968), Altman(1968), and Zmejewski (1984). Intuitively, this study concluded that the poorfinancial performances have already long been suffered by companies listed inASEAN country capital markets before the monetary crisis. The crisis has just openedthe hidden problems.